Joint association of polysocial risk score and lifestyle with incident essential hypertension: a prospective cohort study in the UK biobank - Yumei Zhao; Yingbai Wang; Zihan Xu; Jiaofeng Xiang; Chuxun Zhou; Xiaolin Li; Shicai Ye; Suru Yue; Xuefei Hou; Jia Wang; Jiayuan Wu (BMC Cardiovascular Disorders)
Abstract Background The polysocial risk score (PsRS) estimates cumulative social vulnerability. While social factors and lifestyles are linked to essential hypertension (EH), their combined effects are unclear. This study aims to explore the independent and joint associations of social vulnerability and lifestyle with EH in the UK Biobank Study. Methods The study included 131,154 UK Biobank participants without EH at baseline. PsRS was calculated from 14 social determinants across three risk categories: socio-economic, psychological, and environmental factors, all significantly linked to EH development after Bonferroni adjustment. The healthy lifestyle score was based on smoking, alcohol, physical activity, diet, and sleep. The Cox proportional hazards model with HR and 95% CI analyzed PsRS and lifestyle effects on EH incidence, and interactions between PsRS and lifestyle score were assessed additively and multiplicatively. Results Over an average follow-up of 13.5 years, 19,281 participants (14.7%) developed EH. After adjusting for confounders, participants with intermediate (5,–7) and high (≥ 8) PsRS exhibited increased EH risks with HRs of 1.06 (95% CI: 1.02–1.10) and 1.15 (95% CI: 1.11–1.20), respectively, compared to those with low PsRS (≤ 4). In the fully adjusted model, every one-point increase in PsRS was associated with a 7.0% higher risk of EH (HR = 1.07, 95% CI: 5.0–9.0, P for trend < 0.001). Intermediate (2–3) and favorable (4–5) lifestyle scores were associated with lower EH risks, with HRs of 0.86 (95% CI: 0.82–0.90) and 0.77 (95% CI: 0.73–0.81), respectively, compared to an unfavorable lifestyle score (0–1). Each one-point decrement in lifestyle score was corresponded to a 14% reduced in EH risk (HR = 0.86, 95% CI: 0.84–0.89, P for trend < 0.001). Joint effects analysis revealed significant synergistic interactions with individuals possessing both high PsRS and unfavorable lifestyles experienced the greatest risk (HR = 1.47,95% CI: 1.37–1.58). Additive interaction metrics confirmed this synergy, indicating 66% of EH risk in this subgroup stemmed from PsRS-lifestyle interaction. Multiplicative interactions were likewise significant (P interaction<0.001). Conclusion An unhealthy lifestyle may exacerbate the impact of social vulnerability on EH risk. Modifying both social vulnerability and lifestyle factors could reduce EH incidence.